On the Range of Persons providing Qualified Legal Assistance - ZULEYEVA, Ainagul Zhanilbekovna (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The paper covers problematic issues of identifying persons providing qualified legal assistance. The author examines the current legislation of the Republic of Kazakhstan, in which the notion of qualified legal assistance is fixed. Meantime, the right to qualified legal assistance is regarded as one of the most important existing constitutional guarantees of rights and freedoms of a human and a citizen. The author analyzes the existing points of view on the content of the constitutional right to qualified legal assistance, positions of scientists and experts on the mechanism to implement the rights and range of parties concerned. The article also provides the experience of foreign countries in this field. Priority attention is given to the analysis of the provisions of the Criminal Code of the Republic of Kazakhstan, where one of the articles provides for criminal liability for abuse of powers by private notaries, appraisers, private bailiffs, mediators and auditors working in audit organizations. The study leads to the conclusion that the only basis to unite such diverse parties is the commonality of their functions in connection with the provision of qualified legal assistance. The author draws attention to the vagueness of the criteria in identifying the parties in that norm of the Criminal Code, rationalizing the proposals on improvement of the existing legislation in this area.